Risk factors for Aedes aegypti household pupal persistence in longitudinal entomological household surveys in urban and rural Kenya - Harun N. Ngugi; Sindiso Nyathi; Amy Krystosik; Bryson Ndenga; Joel O. Mbakaya; Peter Aswani; Peter S. Musunzaji; Lucy W. Irungu; Donal Bisanzio; Uriel Kitron; A. Desiree LaBeaud; Francis Mutuku (Parasites & Vectors, 2020)
Abstract Background Aedes aegypti is an efficient vector of several arboviruses of public health importance, including Zika and dengue. Currently vector management is the only available avenue for disease control. Development of efficient vector control strategies requires a thorough understanding of vector ecology. In this study, we identified households that are consistently productive for Ae. aegypti pupae and determined the ecological and socio-demographic factors associated with the persistence and abundance of pupae in households in rural and urban Kenya. Methods We collected socio-demographic, environmental and entomological data monthly from July 2014 to June 2018 from 80 households across four sites in Kenya. Pupae count data were collected via entomological surveillance of households and paired with socio-demographic and environmental data. We calculated pupal persistence within a household as the number of months of pupal presence within a year. We used spatially explicit generalized additive mixed models (GAMMs) to identify the risk factors for pupal abundance, and a logistic regression to identify the risk factors for pupal persistence in households. Results The median number of months of pupal presence observed in households was 4 and ranged from 0 to 35 months. We identified pupal persistence in 85 house-years. The strongest risk factors for high pupal abundance were the presence of bushes or tall grass in the peri-domicile area (OR: 1.60, 95% CI: 1.13–2.28), open eaves (OR: 2.57, 95% CI: 1.33–4.95) and high habitat counts (OR: 1.42, 95% CI: 1.21–1.66). The main risk factors for pupal persistence were the presence of bushes or tall grass in the peri-domicile (OR: 4.20, 95% CI: 1.42–12.46) and high number of breeding sites (OR: 2.17, 95% CI: 1.03–4.58). Conclusions We observed Ae. aegypti pupal persistence at the household level in urban and rural and in coastal and inland Kenya. High counts of potential breeding containers, vegetation in the peri-domicile area and the presence of eaves were strongly associated with increased risk of pupal persistence and abundance. Targeting households that exhibit pupal persistence alongside the risk factors for pupal abundance in vector control interventions may result in more efficient use of limited resources.